Supporting Factors for the Spread of the Hanafi School throughout the World - Meirison Meirison; Testru Hendra (Muqaranah, 2022)
Abstract: The doctrine of Abu Hanifa has spread in the country since Abu Yusuf empowered him after assuming the position of judge of judges in the Abbasid state. It was the official doctrine of it, in addition to the philosophy of Malik in the Hijaz. The Hanafi school became the only official school of thought when Malik died. It spread in Iraq and its east from the countries of the Persians: Persia and Beyond the River (Turkistan), Afghanistan, and India. It was also the official doctrine of many Levantine countries, such as the Seljuk State, the Gharnawi State, and the Ottoman State. Then they began to push people to embrace its doctrine until it became the most prominent Islamic school of thought with followers among Muslims due to the length of the rule of the Ottoman Empire, which spanned about seven centuries. Instead, they even imposed the recitation of Hafs on the authority of Asim, instead of the recitations that are widespread in the Islamic world (especially the recitation of al-Dawri), just because Abu Hanifa used to recite it! The Turks spread their doctrine in eastern Europe, Iraq, and northern Syria, but they failed to impose it in areas far from their influence, such as the island and Africa.